Factors Influencing Online Health Information Acquisition Behavior of Rural Elderly Groups in Western China: A Field Study from the Guanzhong Region of Shaanxi Province - Zheng WANG, Miao ZHUANG, Yudi ZHANG, Yaqi ZHANG (Nongye tushu qingbao xuebao)
[Purpose/Significance] As China's population ages, the health status and information accessibility of rural elderly groups have become the focus of public attention. This study aims to explore the factors influencing the online health information access behavior of the elderly in rural areas of western China, with the aim of improving the current situation of this group's access to information, increasing the efficiency of their access to health information, narrowing the digital divide, and providing references for promoting the "Healthy China 2030" strategy. [Method/Process] Thirteen rural villages in the Guanzhong region of Shaanxi province were selected as the research sites to collect primary data through face-to-face in-depth interview. Based on the grounded theory and three-level coding with the help of qualitative analysis software NVIVO, we constructed a model of factors influencing the access to health information among the rural elderly in western China by taking into account the three behavioral modes of health information search, health information encounter, and health information substitution search. [Results/ [Conclusions] The health information seeking behaviors of western rural elderly groups were influenced by information, personal factor, social factor and media. Among them, the cultural level, media literacy, and subjective perception of personal factors directly affect the demand for and access to health information by the elderly; medical concepts are more influenced by social factors. Social factors, such as family support, social networks, and the availability of local healthcare resources significantly influence how older adults access health information and its effectiveness. Content specificity and quality reliability of information factors are key factors that drive or hinder older adults' willingness to access online health information. The media, as an external context, plays a mediating role in older adults' active or passive access to health information, with short video platforms and social media in particular becoming important channels. In addition, the study found that the roles of health information acquisition among the rural elderly could be categorized into passive recipients, limited participants and active searchers of health information, and based on this, a three-dimensional "R-P-S" model was constructed to describe the online health information acquisition status of the rural elderly. This model represents the developmental trajectory of this group's online health information access status, and as health information literacy improves, individuals may move from one stage to another more mature stage. Finally, interventions for different roles in health information access are proposed to better meet the health information needs of the rural elderly population.